Prevalence and factors associated with fire outbreak among traders in Kwari market, Kano - Usman Muhammad Ibrahim; Abdulmuminu Bashir Umar; Auwal Umar Gajida; Sunday Audu; Rabiu Ibrahim Jalo; Abba Ahmed Danzomo; Fatimah Ismail-Tsiga Ahmed; Kabiru Abdulsalam; Usman Bashir; Abubakar Muhammed Jibo (Ntec Specialist, 2022)
Background: Fire outbreak in business places can result in losses in production, unemployment, morbidity and mortality and significant psycho-social problems Objective: This study aimed to determine the prevalence, socio-demographic and other factors associated with fire outbreaks amongst traders in Kwari market, Kano state. Methodology: Adescriptive cross-sectional study design was used to study 442 traders in Kwari market, selected using a two-stage sampling technique. Data were collected using intervieweradministered questionnaires and analyzed using SPSS version 22.0 with P ≤ 0.05 considered to be statistically significant. Results: A total of 442 traders were studied. The age of the traders ranged between 18 and 70 years with a mean± SD of 38.3±9.8 years. Majority of the traders 416 (94.1%) and 425 (96.2%) were greater than or equal to 24 years of age and were males respectively. Only 21 (4.8%) of them acquired post-secondary educational qualification. The prevalence of fire outbreak among the traders was 73(16.5%). Significantly higher fire outbreak (17.5%, p=0.02) was found among traders aged 24 years and above. Similarly, male sex (15.5%, p=0.05), secondary level education (16.8%, p=0.001), cleaning job (24.4%, p=0.02) were significantly associated with higher fire outbreak. A significantly higher fire outbreak (17.6%, p=0.03) was found among traders with no prior knowledge of the need for safety guidelines and emergency contact numbers. Ever having power fluctuations in the shop was associated with 35folds increased in likelihood of fire outbreak {aOR= 35, 95%CI= (4.8-257)} while not having firefighting equipment currently was associated with two folds increased in likelihood of fire outbreak {aOR=2.0, 95%CI= (1.2-2.3)}. Conclusion: The prevalence of fire outbreaks is high and significantly associated with socio-demographic factors and poor fire safety practices, therefore all the relevant stakeholders should ensure the enforcement of fire control guidelines among traders.